German librarians in 1789–1871. Personal features of librarians - Gębołyś, Zdzisław (Interdyscyplinarium nauk o mediach i kulturze, 2020)
Personal characteristics are an important factor in library work. Personal success depends on the success or failure of the library, both from the perspective of the individual and the institution. The element of time and space is in this case a secondary issue. The subject of the study are the personal features of German librarians who were professionally active in the years 1789–1871. The analysis covered the librarians of the three most important types of libraries of the period: university libraries, court libraries and city libraries. The main attention is paid to the negative behavior of librarians, as they have an extremely fatal impact on the image of the library in society. The examples of serial and prominent librarians show the effects of negative behavior, especially in human relations, i.e. between library employees and between librarians and readers.